Macromarketing Issues on the Sidewalk: How "Gleaners" and "Disposers" (Re)Create a Sustainable Economy. (September 2014) - Guillard, Valérie; Roux, Dominique
The aim of this research is to show that though French public policy advocates sustainable development, it unwittingly deters non-institutionalized sustainable practices. To illustrate this paradox, this research focuses on bulky item collection and the urban gleaning to which it gives rise. A qualitative study shows that urban gleaning comes into conflict with the hygiene norm that pre-exists concerns about sustainability. To ease these tensions and authorize themselves to glean, gleaners draw on a repertoire of justifications around sustainability that condemns waste and attributes altruistic intentions to disposers. In turn, to put their items out on the sidewalk, disposers must negotiate tensions in relation both to the hygiene norm (not polluting public space) and to the sustainability norm (not throwing away items that could still be used by other people). To justify their act, disposers construct an image of gleaners, to whom they can "pass on" their possessions. This double process appears to create a new form of sustainable circulation through which objects are redistributed and which has important implications for macromarketing.